2000
DOI: 10.3136/fstr.6.102
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of Rice Paper of Vietnamese Traditional Food (Vietnamese Spring Rolls).

Abstract: Rice papers made of non-glutinous rice are a common food item in Vietnam and Thailand. Called as Banh Da Nem in Vietnam, rice papers are used very often in the making of a traditional dish called Nem, i.e., Vietnamese spring rolls. The amino acid content in the rice papers extracted with water was found to be 2 to 3 fold higher than that in cooked rice, showing that the protein was resolved by microbial enzymes during the rice paper processing. Among organic acids, Iactic acid is most common in rice papers, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…It is consistent with the reports on fermented rice noodles in other countries (Uchimura et al. 1991; Nagano et al. 2000; Ikeda et al.…”
Section: Discussionsupporting
confidence: 93%
“…It is consistent with the reports on fermented rice noodles in other countries (Uchimura et al. 1991; Nagano et al. 2000; Ikeda et al.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding rice paper produced from untreated flour, Nagano et al (2000) [11] found that the Japanese rice paper produced from low-amylose rice (Akebono variety) had 6.94% crude protein, and 17.52% amylose, which is close to our results. For rice papers produced from hydrothermal treated flours, a significant decrease was found in protein, total starch, and amylose contents.…”
Section: Chemical Composition Of Broken Rice Flour and Untreated And supporting
confidence: 91%
“…But, it is not popular in Arab countries, especially in Egypt. Rice paper is a large variety of filled, rolled appetizers as spring roll papers [11] or güllaç/ golash produced from wheat flour. The type of wrapper, fillings, and the cooking method used, as well as the name, differ considerably inside this large zone, according the culture of the area [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…noodles made from aged rice by natural fermentation have a better texture and mouthfeel during eating than noodles made by nonfermented methods (Uchimura et al 1991;Nagano et al 2000;Ikeda et al 2003;Lu et al 2003Lu et al , 2005. It is worthwhile exploring fermentation technology for expanding traditional production to an industrial scale and developing new rice noodle production technology.…”
mentioning
confidence: 99%